2018
DOI: 10.2319/111317-773.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fixed orthodontic appliances on nonmicrobial salivary parameters

Abstract: Exposure to fixed orthodontic appliances did not show a significant effect on salivary parameters related to inflammation or stress, with the exception of a significant but transient pH decrease after bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…After ZOGAKIS & al. [24], oxidant-scavenging abilities was decreased but not statistically significant (at baseline, one-hour after bonding and after 4-6 weeks) and exposure to fixed orthodontic appliances did not show a considerable effect on salivary parameters related to inflammation or stress. YOUNESS & al.…”
Section: Discussionmentioning
confidence: 74%
“…After ZOGAKIS & al. [24], oxidant-scavenging abilities was decreased but not statistically significant (at baseline, one-hour after bonding and after 4-6 weeks) and exposure to fixed orthodontic appliances did not show a considerable effect on salivary parameters related to inflammation or stress. YOUNESS & al.…”
Section: Discussionmentioning
confidence: 74%
“…Several previous studies evaluated the effect of fixed orthodontic appliance on salivary pH. They compared the changes before and after treatment without specifying which type of ligature materials were used [ 12 , 16 , 17 , 25 , 31 , 33 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fixed orthodontic appliances on salivary pH has been investigated in previous studies without reporting which type of archwire ligation material was used. In an observational study, Zogakis et al [ 25 ] demonstrated a significant decrease in pH of saliva six weeks after fitting the appliance. Different results were presented by Peros et al [ 26 ] who reported an increase in salivary pH at 6, 12 and 18 weeks after fixed orthodontic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The effect of the xed orthodontic appliances on salivary pH has been investigated in previous studies without reporting which type of archwire ligation material was used. In an observational study, Zogakis et al 25 demonstrated a signi cant decrease in pH of saliva six weeks after tting the appliance. Different results were presented by Peros et al 26 who reported an increase in salivary pH at 6, 12 and 18 weeks from therapy.…”
Section: Trial Registrationmentioning
confidence: 98%